A Conceptual Model on Digital Entrepreneurship: Perspective of Smart Organization and Technological Innovation - Eneizat , Mushira A.; Al-Kassabeh , Mohammed M. (New Innovations in Economics, Business and Management Vol. 8, 2022)
Innovation is the only way to preserve development and competitiveness in today's world of rapid and increasing change. For organizations to succeed in the midst of those complexes, accelerating changes, adopting innovation remains the best option to maintain growth and competitiveness. That is why organizations need to be “smart” on the ground, i.e. to work through technology driven by knowledge and learning. They also need to be resilient to create innovative ideas stemming from within and exploit external opportunities. Organizations actually need to become "smart" to confront the growing customer needs, and changing markets. Digital entrepreneurship (DE) is perceived as a key pillar for innovation. However, there are a number of concerns surrounding smart organization (SO), Digital entrepreneurship (DE), and technological innovation (TI), and how they are related is complex and important to understand in this digital age. The benefits of innovations is reflected on the individuals, society, industry, and businesses. What is common among all of these entities is that they all aim at innovation and strive for it diligently, in order to prepare optimally for a prosperous future. Innovation should be intelligent through constant preparedness to face the uncertain future, learning, knowledge, adaptation, and agility. Innovation should also be effective in creating smart organizations based on AI, intelligence at work, creative orientation, environment understanding, adaptation, and continuous learning, which would enhance the innovation of products, processes, modern methods of payment, etc. Based on conducting a deep literature review, this study proposes a conceptual model for SO focusing on TI (i.e. Product and process). This integrated paradigm claims that SO's components, such as business intelligence, creative orientation, comprehension of the environment, adaptation, and continual learning, all play a vital role in TI. Furthermore, it is proposed that DE acts as a mediator between the SO and the TI. The creation of hypotheses and the suggestion of new study fields are explored.